PERFORMANCE OF MEAT-TYPE DUCKLINGS ON DIFFERENT LEVELS OF FEED RESTRICTION - Parilla, Ebenezer T. (Annals of Tropical Research, 1984)
Body weights were reduced when ducklings were subjected to restricted feeding. However, no significant differences in body weights were obtained among treatments at 9 weeks old. The average fasted weights, uneviscerated weights, carcass weights (with and without giblets), and dressing percentages as well as the percentage of cut-up parts such as thighs, drumsticks, wings, neck, tail-back and rib-back were not significantly affected by feed restriction. However, the breasts of fully-fed ducklings were heavier and had higher percentage values than those of the restricted ducklings. Feed restriction also did not statistically influence the weights and percentage values of the giblets, head, blood, shanks and intestines. Highest returns-above-feed-and-duckling-costs can be derived when ducklings are marketed at 6 weeks of age. Ducklings whose feeds were restricted had higher returns-above-feed-and-duckling-costs than the fully-fed ducklings at later stages.